2004
DOI: 10.1002/food.200300352
|View full text |Cite
|
Sign up to set email alerts
|

In vitro starch digestibility changes during storage of maize flour tortillas

Abstract: Nixtamalized maize flours elaborated by four factories in Mexico were used for tortilla preparation. Samples were stored at 4 degrees C for up to 72 h and their in vitro starch digestibility features were evaluated. Moisture content was different between flour and tortilla but no evident relation could be established. Protein and lipid levels were lower in tortillas than in flour but ash content was not different in both samples. A decrease in available starch content was observed upon 48 h cold storage (4 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 18 publications
(29 reference statements)
9
36
0
Order By: Relevance
“…There were no significant (P > 0.05) differences in the total ash content in either type of tortillas supplemented with different levels of chia powders (Table 1). The ash content found in the chia seed-added tortilla was higher than that reported for conventional tortillas (Agama-Acevedo et al 2004). Islas-Hernández et al (2007) reported similar values for tortilla fortified with amaranth, 1.4% in tortilla from 100% maize and 1.5% for corn/amaranth tortilla.…”
Section: Proximate Analysesmentioning
confidence: 65%
See 3 more Smart Citations
“…There were no significant (P > 0.05) differences in the total ash content in either type of tortillas supplemented with different levels of chia powders (Table 1). The ash content found in the chia seed-added tortilla was higher than that reported for conventional tortillas (Agama-Acevedo et al 2004). Islas-Hernández et al (2007) reported similar values for tortilla fortified with amaranth, 1.4% in tortilla from 100% maize and 1.5% for corn/amaranth tortilla.…”
Section: Proximate Analysesmentioning
confidence: 65%
“…These results show that the starch present in the tortillas is available for hydrolysis by the digestive enzymes used in this method, because it includes a boiling/Termamyl treatment that converts native resistant granules in digestible starch. The AS contents determined in chia seed-added tortilla were lower than those determined in tortilla prepared with nixtamalised corn flour (66-76%) (Agama-Acevedo et al 2004) and in masa-made tortilla (67-76%) (AgamaAcevedo et al 2005). The AS value is important due to its ability to supply glucose to the blood after the meal consumption.…”
Section: In Vitro Digestibility Testsmentioning
confidence: 96%
See 2 more Smart Citations
“…An increase in the protein content was observed with respect to the level of flaxseed added to the tortilla. Flaxseed flour has 21% higher protein level (Ramcharitar, Badrie, Mattfeldt-Bemam, Matsuo, & Ridley, 2005) than that in the NCF (9.33%) (Agama-Acevedo et al, 2004), which influenced this parameter. Figueroa et al (2001) observed 3% higher protein content when the tortilla was fortified with 4% of defatted soy.…”
Section: Proximate Analysesmentioning
confidence: 97%